Work from home: Leadership style and work performance in the context of Covid-19 - Rodriguez Pecho, Neir Franci; Chocce Lopez, Presila; Acosta Enriquez, Benicio Gonzalo; Huamani Jordan, Olger; Villena Zapata, Luigi Italo; Vilcapoma Pérez, César Robin; Alor Minaya, Daniel (LACCEI, 2023)
The objective of the study was to determine the relationship between leadership style and job performance of supervisors of a company in the city of Lima, in the context of the work from home - WHF modality. The research was quantitative, of non-experimental design, of correlational-cross-sectional scope, two questionnaires were applied to 230 employees and 30 supervisors of the company Multiservicioscall. It is concluded that: (1) The type of leadership style is directly or inversely related to work performance, depending on the style that predominates in the employees and supervisors of the Multiservicioscall company in the context of working from home due to the Covid-19 pandemic. (2) The predominant leadership styles in the multiservicioscall company are Democratic and Laissez Faire, being found in the medium and high levels. (3) The collaborators denote an optimal work performance in the context of WHF, given that the dimensions of social ability, professional motivation and work commitment present the highest scores in the medium and high levels, respectively.